DETERMINISMO Y CONTINGENCIA EN LA OBRA HISTORIOGRÁFICA DE PROCOPIO CESARIENSE: LA SIGNIFICACIÓN DE TYCHE Y ZEOS - Marín Conesa, Rita (Antigüedad y Cristianismo, 1995)
In Late Antiquity, due to the influence of the Jewish Christian monotheism, the pagan notion of «destiny» undenvent an ideological revolution. The human actions continued to be directed by Tyche, as can be seen in the works of the historian Procopio Casariense, but the incomprehensible behaviour of «Fortuna» manifests itself nore as part of a pre-established divine model. Therefore, according to the Christian thinking, Tyche governed History but subordinated to «God's plan». Later the notion of Tyche is considered as a simple manifestation of the divine Logos. (...)